Naturalized distributions show that climatic disequilibrium is structured by niche size in pines (Pinus L.). Issue 4 (13th December 2018) - Perret, Daniel L.; Leslie, Andrew B.; Sax, Dov F.
Abstract: Aim: The assumption that the native distributions of species are in equilibrium with climate has been shown to be frequently violated, despite its centrality to many niche model applications. We currently lack a framework that predicts these violations. Here, we examine whether variation in climatic disequilibrium is structured by properties of species' native distributions and climatic niches. Location: Global. Methods: We built climatic niche models for 106 pine ( Pinus L.) species, including 25 that have naturalized outside their native range. We measured the extent of climate space occupied exclusively by naturalized populations and considered what fraction of this space was available within the native continent and near the native range. We examined the consequences of disequilibrium for estimates of potential range filling and sister species niche conservatism. Results: Most species (23 of 25) have naturalized in climate conditions outside the native niche, leading to increases in the total known suitable climate space. Increases in niche size were negatively related to native niche size. Increases were often large; one species expanded its niche by almost 10% of the global climate space. These increases were associated primarily with cooler, wetter and less seasonal climates. Increases in known niche size lowered potential range filling estimates within species' native continent and ecoregion. Naturalized data did not strengthen support for niche conservatism among sister species. Main conclusions: Among pines, climatic disequilibrium is the norm and not the exception. The magnitude of this disequilibrium can be vast, such that the native range greatly under‐represents the true climatic tolerances of some species. Fortunately, this disequilibrium can be predicted largely by the size of a species' native niche. Accounting for this disequilibrium can improve our ability to characterize ecological phenomena, including potential range filling. This is an essential step towards improving the conservation value of ecological niche models.